A randomized controlled trial in non-responders from Newcastle upon Tyne invited to return a self-sample for Human Papillomavirus testing versus repeat invitation for cervical screening. (March 2015) - Cadman, Louise; Wilkes, Scott; Mansour, Diana; Austin, Janet; Ashdown-Barr, Lesley; Edwards, Rob; Kleeman, Michelle; Szarewski, Anne
Background: Non-attenders for cervical screening are at increased risk of cervical cancer. Studies offering self-sampling for high-risk Human Papillomavirus (HrHPV) testing have shown greater uptake than sending another invitation for cytology. Objectives: To explore whether uptake would increase in a less diverse, more stable population than the previous English study, which demonstrated a lower response rate than other studies. The primary objective was whether non-attenders were more likely to respond to a postal invitation, including kit, to collect a self-sample compared with a further invitation for cytology screening. The secondary objective was whether women with an abnormal result would attend for follow-up. Methods: 6000 non-attenders for screening in this pragmatic, randomized (1:1) controlled trial in Newcastle-upon-Tyne were sent an HPV self-sample kit (intervention) or a further invitation for cytology screening (comparator). Results: 411(13%) responded to the intervention, returning a self-sample (247(8%)) or attending for cytology (164(5%)), compared with 183(6%) attending for cytology, relative risk 2.25 (95% CI 1.90–2.65) (comparator arm). Of those testing hrHPV positive (32(13%)), 19(59%) subsequently attended cytology screening. Of those in the intervention group who attended for cytology screening without returning an hrHPV self-sample (n = 164), 5% (n = 8) were referred for colposcopy - all attended. In the comparator group eight of the nine referred for colposcopy attended. Conclusion: Persistent non-responders to invitations for cervical screening are significantly more likely to respond to a postal invitation to return a self-collected sample for HPV testing than a further invitation for cytology screening. However, just over half followed up on this positive HPV result.